2013
DOI: 10.1007/s00520-012-1709-z
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and predictors of mortality in patients requiring invasive mechanical ventilation due to acute respiratory failure while undergoing ambulatory chemotherapy for solid cancers

Abstract: The outcome of patients with acute respiratory failure needing invasive mechanical ventilation during ambulatory chemotherapy for solid cancer is poor. Prechemotherapy performance status is an independent predictor of mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 38 publications
0
11
0
3
Order By: Relevance
“…All studies were published in English (MeSH term of our research). Study populations varied across studies, including four studies focusing on cancer patients [21, 23, 34, 39], fourteen on patients with hematological malignancies, and the remaining on various mixes of these underlying diseases. Outcome variables included ICU mortality in 13 studies, hospital mortality in 24 studies, and 6-month mortality in a single study.…”
Section: Resultsmentioning
confidence: 99%
“…All studies were published in English (MeSH term of our research). Study populations varied across studies, including four studies focusing on cancer patients [21, 23, 34, 39], fourteen on patients with hematological malignancies, and the remaining on various mixes of these underlying diseases. Outcome variables included ICU mortality in 13 studies, hospital mortality in 24 studies, and 6-month mortality in a single study.…”
Section: Resultsmentioning
confidence: 99%
“…This finding is compatible with most of the other researches. 28,29 Namendys et al reported IMV not to be associated with increased ICU mortality in ST patients but this study included postoperative patients. 26 NIMV is a way of reducing the requirement for IMV.…”
Section: Resultsmentioning
confidence: 90%
“…A weakness in our model is that it does not include an assessment of patient performance status (e.g. Eastern Cooperative Oncology Group Performance Scale), which is known to correlate with survival for various malignancies [28]. This is because performance status was rarely available during retrospective review of our electronic medical record for our patient cohort at the time of filter implantation.…”
Section: Discussionmentioning
confidence: 99%